The influence of thermal treatment conditions on the properties of TiO2 ceramics. (1st June 2014) - Narkevica, Inga; Ozolins, Jurijs; Rubenis, Kristaps; Kleperis, Janis; Locs, Janis; Berzina-Cimdina, Liga
Abstract : The influence of thermal treatment conditions on titanium dioxide ceramics phase transformation, microstructure, physico-mechanical and electrical properties was studied. TiO2 ceramic was prepared using extrusion technology and thermal treatment in air and subsequent annealing under high vacuum conditions. It has been observed that intense TiO2 ceramic mass sintering occurs over the temperature ranging from 950 °C to 1100 °C. It is accompanied by crystallographic modification change from anatase to rutile. Ceramic sample annealing in vacuum causes formation of nonstoichiometric titanium oxide ceramics and as a result electrical conductivity of the material significantly increases. Using extrusion process relatively dense and mechanically resistant ceramic material can be obtained that can be used in different technological processes.